Ondel-ondel: ethno-physics-based learning media to achieve meaningful learning on rigid body equilibrium material - Dwi Susanti; Slamet Maulana (Universitas Sultan Ageng Tirtayasa, 2023)
Ondel-ondel is one of the well-known local cultures from Jakarta. However, the role of ondel-ondel is not only in switching ceremonies and rituals but can be used as learning media. In addition to local cultural problems that are still not optimal in learning, the learning process must be carried out meaningfully. So, this study aims to analyze ondel-ondel culture from the point of view of Physics (especially on rigid body equilibrium material) and to implement it as learning media in Physics learning to achieve meaningful learning. This research is a mixed method research. Based on the results and discussion obtained, ondel-ondel has many physics concepts. In ondel-ondel, rigid body equilibrium is of special concern because equilibrium is the main focus so that the ondel-ondel remains stable when played without falling. In ondel-ondel culture, the concept of circular motion and heat also applies. The second conclusion obtained from this study is that the implementation of ondel-ondel as a learning medium is proven to realize meaningful learning for students. Achieving meaningful learning through implementing an ondel-ondel as learning media has very good criteria.